Effect of Seedling Diameter on Growth of Transplanted Silver Fir Seedlings in the Nursery - Singh, R. V.; Sharma, K. C. (Indian Forester, 1981)
In an experiment conducted to study the effect of seedling diameter on the growth of transplanted silver fir seedlings in the nursery, studies were made on the growth and survival of seedlings of four classes, viz., < 1.5,1.5- <, ’2.0’, 2.0- <2.5 and 2.5 - <3.0 mm diameter. The performance of the seedlings of < 1.5 mm diameter both in term, of survival and growth was poorer than that of those of the remaining three classes which did not differ significantly from each other. Seedlings of < 1.5 mm diameter should, therefore, be called at the time of transplanting.